2007
DOI: 10.1016/j.ijsolstr.2006.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Rupture mechanisms in combined tension and shear—Experiments

Abstract: An experimental investigation of the rupture mechanisms in a mid-strength and a high-strength steel were conducted employing a novel test configuration. The specimen used was a double notched tube specimen loaded in combined tension and torsion at a fixed ratio. The effective plastic strain, the stress triaxiality and the Lode parameter were determined in the centre of the notch at failure. Scanning electron microscopy of the fractured surfaces revealed two distinctively different ductile rupture mechanisms de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
212
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(230 citation statements)
references
References 17 publications
17
212
0
1
Order By: Relevance
“…This behavior is in agreement with the numerical results published by other authors [11,27]. Several authors [22][23][24][25][26] have assumed a symmetric failure criterion concerning the Lode parameter.…”
Section: Resultssupporting
confidence: 90%
“…This behavior is in agreement with the numerical results published by other authors [11,27]. Several authors [22][23][24][25][26] have assumed a symmetric failure criterion concerning the Lode parameter.…”
Section: Resultssupporting
confidence: 90%
“…Recently, several studies [12][13][14][15][16][17][18][19][20][21] have shown that the Lode angle, associated with the third invariant of the deviatoric stress tensor, is an essential parameter in ductile fracture. It characterizes the effect of the stress state on plastic flow and the ductile rupture of the material.…”
Section: Introductionmentioning
confidence: 99%
“…The true fracture strain is the most physical experimental indicator for quantifying the resistance to damage and fracture of a material subjected to tensile loading conditions. An average true fracture strain measure f  using the diameter reduction is usually used to quantify the ductility [9,10]. It is defined as 2 log ⁄ .…”
Section: Rounded Smooth Bar Tensile Testmentioning
confidence: 99%
“…In addition, if void nucleation is disregarded, the GTN model cannot describe ductile failure evolution for shear stress close to zero since, according to this constitutive model, the void growth mechanism requires hydrostatic tension within the material. However, continued softening and then ductile failure is known to occur at low triaxiality and even in situations of pure shear [9,10].…”
mentioning
confidence: 99%